PEMBELAJARAN TIDIDA'A MENGGUNAKAN METODE DRILL PADA KEGIATAN EKSTRAKURIKULER SISWA KELAS X APL-2 DI SMK NEGERI 1 GORONTALO - Potale, Sabina Putri Aulia; Djafar, Nurlia; Ohi, Rahmawati; Sitharesmi, Riana Diah; Karlan, La Ode (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research is based on the problems encountered in the implementation of extracurricular activities in dance, particularly among students in class X APL-2 at SMK Negeri 1 Gorontalo, which has not been maximized. The researcher found several problems in the implementation of extracurricular activities, where students in class X APL-2 still lack understanding of dance movements, especially the Tidi Da'a dance. During extracurricular activities, students mostly practice independently without direct guidance from the extracurricular coach. This can be seen from the students' stiffness in performing dance movements, resulting in a lack of synchronization between one movement and the next. Given these problems, the researcher used the drill method in the learning process of Tidi Da'a in extracurricular activities, aiming to observe and describe the extent of the application and effectiveness of the drill method in learning Tidi Da'a among students in class X APL-2 at SMK Negeri 1 Gorontalo. To solve the problems in this research, several theories were used, including the concept of learning and the drill method. The purpose of this study is to describe the learning process of the traditional Tidi Da'a dance in extracurricular activities. The results of the research show that the drill method is very effective during the practice process of the Tidi Da'a dance. It can be concluded that this research shows that the effectiveness of the drill method has a significant impact on the learning process, as evidenced by the students' responsibility in carrying out the tasks and exercises given, although some students still make mistakes, such as unstable tempo. In the evaluation process, each student is able to perform the dance well